VOLUME USING LAYERED MODEL DESCRIPTION OF THE PHENOMENON OF ADSORPTION PHYSICS MULTICAPAS - Tapia-Huanambal, N. (2000)
We shall adopt a physical model in which the adsorben! surface and the properties of each of the layers are uniform. Full allowance is made for interactions within each layer. This interaction gives rise to the phase transition within the layer. Allowance for the interaction between layers is made through the dimensional defect of chemical potential.